Percutaneous thoraco-lumbar-sacral pedicle screw placement accuracy results from a multi-center, prospective clinical study using a skin marker-based optical navigation system - Scarone, Pietro; Chatterjea, Anindita; Jenniskens, Inge; Klüter, Tim; Weuster, Matthias; Lippross, Sebastian; Presilla, Stefano; Distefano, Daniela; Chianca, Vito; Sedaghat, Sam; Nelson, Melissa; Lampe, Finn; et al. (European spine journal, 2022)
Study design Prospective multi-center study. Objective The study aimed to evaluate the accuracy of pedicle screw placement using a skin marker-based optical surgical navigation system for minimal invasive thoraco-lumbar-sacral pedicle screw placement. Methods The study was performed in a hybrid Operating Room with a video camera-based navigation system integrated in the imaging hardware. The patient was tracked with non-invasive skin markers while the instrument tracking was via an on-shaft optical marker pattern. The screw placement accuracy assessment was performed by three independent reviewers, using the Gertzbein grading. The screw placement time as well as the staff and patient radiation doses was also measured. Results In total, 211 screws in 39 patients were analyzed for screw placement accuracy. Of these 32.7% were in the thoracic region, 59.7% were in the lumbar region, and 7.6% were in the sacral region. An overall accuracy of 98.1% was achieved. No screws were deemed severely misplaced (Gertzbein grading 3). The average time for screw placement was 6 min and 25 secs (± 3 min 33 secs). The average operator radiation dose per subject was 40.3 µSv. The mean patient effective dose (ED) was 11.94 mSv. Conclusion Skin marker-based ON can be used to achieve very accurate thoracolumbarsacral pedicle screw placements.